Quando dizer é agir moralmente: uma análise dos atos de fala morais em Hare - Matos, Ana Gabriela Colantoni de (2010)
This dissertation treats about the relation between information and action in moral judgments. First of all, we explicit the logical problem, called antinomy, present in the descriptive ethics theories which do not admit the prescriptive factor of the moral judgments. Secondly we present the logical problem, called paradox, present in Austin s linguistic theory (which gave rise to the ethical prescriptivism) that does not admit the descriptive factor of moral judgments. After that, we present Hare s theory as synthesis, which gathers descriptive and prescriptive factors, and, because of this, does not make the same mistakes of the theories previously developed. Although, some critics - Geach, Sen and Azevedo accused Hare of being an existential descriptivist. More precisely, Sen and Geach accused him of being descriptivist, whereas Sen and Azevedo accused him of being existentialist. This work shows that those accusations occur because of the failure in the interpretation of the relation between descriptive and prescriptive factors on Hare s formulation about moral judgments. For the author, the supervenience (which guarantees that the moral choices must be the same when the same factual elements are presented) is the fundament of the universalizability (which guarantees that the moral action must be the same independently of the roles played on the moral action). However, these formulations do not prevent that the author of the moral judgment gather more information and start acting differently, which would not be possible for a descriptivist. Because of this, we formulated a symbolic model, which relates cultural pattern, prescribed pattern and value; and, moreover, which shows the temporal aspects and the change aspects. Another issue is about the necessity of the critical thought, for Hare, in the formulation of universal ethics. So, this work will explicit the reasons why Hare cannot be called existential descriptivist.